FACTORS AFFECTING THE QUALITY OF LIFE AMONG PULMONARY TUBERCULOSIS PATIENTS: A LITERATURE REVIEW - Febi Septiani; Meira Erawati; Suhartini (Nurse and Health: Jurnal Keperawatan, 2022)
Background: The quality of life for tuberculosis patients remains elusive, affecting their physical, mental, and social well-being. Objectives: The purpose of this scoping review aimed to discuss issues, patient perceptions, and comprehend the impact of pulmonary tuberculosis on the patient's quality of life. Design: This study was conducted by following a scoping framework. Data Sources: This study was carried out following a scoping review framework. This study's literature search relied on data from ScienceDirect, Scopus, EBSCO, ProQuest, ClinicalKey, SpringerLink, ProQuest, and Pubmed. By using the keywords “quality of life” AND “tuberculosis” AND “treatment” OR “perception” OR “experience”. This scoping review leverages a data method derived from 9 articles published between 2016 and 2021. Physical weakness, financial decline, psychological, emotional stress, depression, and stigma experienced by patients are all common problems. Review Methods: The article screening method is used for the review, and it is guided by the PRISMA flowchart. Extraction is carried out on Google Sheets, and synthesis is carried out from the extraction results. Results: This scoping review provides a comprehensive overview of three components of patient impact: 1) physical impact, 2) mental impact experienced by tuberculosis patients, and 3) social impact of tuberculosis patients. There are also six issues to consider: 1) physical disorders (weakness, cough, nausea, vomiting, dizziness, shortness of breath), 2) financial decline, 3) psychological disorders (sad, worried), 4) emotional, 5) depression, and 6) stigma. Conclusion: To enhance the quality of life of Tuberculosis patients, the quality of life must be examined from all perspectives, including physical, mental, and social elements, by intensifying regular health education and self-care management.